Fintech, risk-based thinking and cyber risk - Milena Vučinić; Radoica Luburić (Journal of Central Banking Theory and Practice, 2022)
Financial technology innovations (Fintech) are changing the provision of traditional financial services. Although they bring with them various benefits and opportunities, they also have weaknesses and pose potential threats to financial systems. The paper examines the latest developments in the area of Fintech and outlines the potential benefits and associated risks. It highlights the vital role of the monetary authorities in the context of the policies and initiatives required in order to modernize the financial system, including research and the potential issuance of central bank digital currency, while simultaneously fulfilling their core objectives of preserving monetary and financial stability. The authors highlight the importance of artificial intelligence in Fintech development. They create a Fintech SWOT to support and analyse the above. It goes on further to explain the new management concept of "Risk-based thinking" as a way to approach these potential opportunities and threats of Fintech. Finally, the paper looks at cyber risk in the Fintech landscape as the latest and potentially greatest threat springing from these turbulent and uncertain times.
Keywords: E58; F65; G20; O32; 330; Financial Technological Innovations (Fintech); RiskManagement; "Risk-based thinking"; Cyber risk